Orientation of Pseudomonas aeruginosa ExsA Monomers Bound to Promoter DNA and Base-Specific Contacts with the PexoT Promoter - King, Jessica M; Brutinel, Evan D; Marsden, Anne E; Schubot, Florian D; Yahr, Timothy L (Journal of Bacteriology, 2012)
ExsA is a transcriptional activator of the Pseudomonas aeruginosa type III secretion system (T3SS) and a member of the AraC/XylS protein family. Each of the 10 ExsA-dependent promoter regions that define the T3SS regulon has two adjacent binding sites for monomeric ExsA. Whereas the promoter-proximal sites (binding site 1) contain highly conserved GnC and TGnnA sequences that are separated by ∼10 bp, the promoter-distal sites (binding site 2) share no obvious sequence similarity to each other or to the binding site 1 consensus. In the present study, we used footprinting with Fe-BABE (a protein-labeling reagent that can be conjugated to cysteine residues) to demonstrate that the two ExsA monomers bind to the PexsC, PexsD, PexoT, and PpcrG promoters in a head-to-tail orientation. The footprinting data further indicate that the conserved GnC and TGnnA sequences constitute binding site 1. When bound to site 1, the first helix-turn-helix (HTH) motif of ExsA interacts with the conserved GnC sequence, and the second HTH interacts at or near the TGnnA sequences. Genetic data using the PexoT promoter indicate that residues L198 and T199 in the first HTH motif of ExsA contact the guanine in the GnC sequence and that residue K202, also in the first HTH motif, contacts the cytosine. Likewise, evidence is presented that residues Q248, Y250, T252, and R257 located in the second HTH motif contribute to the recognition of the TGnnA sequence. These combined data define interactions of ExsA with site 1 on the PexoT promoter and provide insight into the nature of the interactions involved in recognition of binding site 2.